A system dynamics model on how zakat can reduce poverty in Indonesia - Setiawan, Danang; Qurtubi, Qurtubi; Khairullah, Rafi (Faculty of Economics, Universitas Islam Indonesia, 2024)
Purpose – This study analyzes the potential of zakat for poverty alleviation using a system dynamics approach. Indonesia has excellent zakat potential as a country with the largest Muslim population. However, the poverty rate in Indonesia is still high at approximately 10.14% of the total population.Methodology – This study used system dynamics to model how zakat can reduce poverty in Indonesia. The system dynamics method was chosen because of its capability to model the complexity of the system. Findings – The model indicates that increasing the percentage of productive zakat allocation and decreasing the delay of the conversion program can reduce the poverty alleviation time from 200 to 120 years using the zakat nisab standard and from 32 years using the Central Statistics Agency (BPS) poverty standard. However, if Zakat faces limited funds, the focus should be on decreasing the conversion delay. Implications –This research can encourage people to become muzakki (zakat payers) because, as indicated in the simulation models, muzakki growth of muzakki has a role in poverty alleviation. In addition, Zakat institutions can use the developed model to simulate the best policy for poverty alleviation before implementing the program.Originality – Although the system dynamics approach has shown promising findings in modeling poverty, the number of studies utilizing system dynamics to analyze the effect of zakat on poverty reduction is limited. Therefore, this study aims to evaluate the effectiveness of zakat in alleviating poverty by implementing a system-based approach and simulating system dynamics.